Agama, Kiai, dan Nasionalisme: Agama, Kiai, dan Nasionalisme - Andi Muhammad Fuad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
Religion and state in Indonesia itself is a separate parts but can be united by referring to several existing concepts so that religion and state, especially Islam, can be united in several things such as tribe, culture, or norms. Islam in Indonesia has long been associated with the State because several elements in Islam can be adopted by the State, for example, nationalism where Islam views nationalism as an important part in the formation of the State of Indonesia and where Kiai plays an important milestone in carrying out nationalism in Indonesia. The research method used in this study is a qualitative research method using a library research approach, The writing method in this paper is a descriptive qualitative method, namely describing a narrative object, with a phenomenological approach, which is related to the phenomena of religion, kiai, and nationalism. The results showed that the relationship between religion, kiai, and nationalism is a relationship that has an important role in building the State so kiai is considered to have an important role in Indonesian independence and the formation of kiai social construction of nationalism.